{-# OPTIONS --without-K --safe #-}
module Data.Nat.Binary.Properties where
open import Algebra.Bundles
open import Algebra.Morphism.Structures
import Algebra.Morphism.MonoidMonomorphism as MonoidMonomorphism
open import Algebra.Consequences.Propositional
open import Data.Bool.Base using (if_then_else_; Bool; true; false)
open import Data.Maybe.Base using (Maybe; just; nothing)
open import Data.Nat.Binary.Base
open import Data.Nat as ℕ using (ℕ; z≤n; s≤s)
open import Data.Nat.DivMod using (_%_; _/_; m/n≤m; +-distrib-/-∣ˡ)
open import Data.Nat.Divisibility using (∣-refl)
import Data.Nat.Properties as ℕₚ
open import Data.Nat.Solver
open import Data.Product using (_×_; _,_; proj₁; proj₂; ∃)
open import Data.Sum.Base using (_⊎_; inj₁; inj₂)
open import Function.Base using (_∘_; _$_; id)
open import Function.Definitions using (Injective)
open import Function.Definitions.Core2 using (Surjective)
open import Level using (0ℓ)
open import Relation.Binary
open import Relation.Binary.Consequences
open import Relation.Binary.Morphism
import Relation.Binary.Morphism.OrderMonomorphism as OrderMonomorphism
open import Relation.Binary.PropositionalEquality
import Relation.Binary.Reasoning.Base.Triple as InequalityReasoning
open import Relation.Nullary using (¬_; yes; no)
import Relation.Nullary.Decidable as Dec
open import Relation.Nullary.Negation using (contradiction)
open import Algebra.Definitions {A = ℕᵇ} _≡_
open import Algebra.Structures {A = ℕᵇ} _≡_
import Algebra.Properties.CommutativeSemigroup as CommSemigProp
import Algebra.Properties.CommutativeSemigroup ℕₚ.+-commutativeSemigroup
as ℕ-+-semigroupProperties
import Relation.Binary.Construct.StrictToNonStrict _≡_ _<_
as StrictToNonStrict
open +-*-Solver
infix 4 _<?_ _≟_ _≤?_
2[1+x]≢0 : ∀ {x} → 2[1+ x ] ≢ 0ᵇ
2[1+x]≢0 ()
1+[2x]≢0 : ∀ {x} → 1+[2 x ] ≢ 0ᵇ
1+[2x]≢0 ()
2[1+_]-injective : Injective _≡_ _≡_ 2[1+_]
2[1+_]-injective refl = refl
1+[2_]-injective : Injective _≡_ _≡_ 1+[2_]
1+[2_]-injective refl = refl
_≟_ : Decidable {A = ℕᵇ} _≡_
zero ≟ zero = yes refl
zero ≟ 2[1+ _ ] = no λ()
zero ≟ 1+[2 _ ] = no λ()
2[1+ _ ] ≟ zero = no λ()
2[1+ x ] ≟ 2[1+ y ] = Dec.map′ (cong 2[1+_]) 2[1+_]-injective (x ≟ y)
2[1+ _ ] ≟ 1+[2 _ ] = no λ()
1+[2 _ ] ≟ zero = no λ()
1+[2 _ ] ≟ 2[1+ _ ] = no λ()
1+[2 x ] ≟ 1+[2 y ] = Dec.map′ (cong 1+[2_]) 1+[2_]-injective (x ≟ y)
≡-isDecEquivalence : IsDecEquivalence {A = ℕᵇ} _≡_
≡-isDecEquivalence = isDecEquivalence _≟_
≡-setoid : Setoid 0ℓ 0ℓ
≡-setoid = setoid ℕᵇ
≡-decSetoid : DecSetoid 0ℓ 0ℓ
≡-decSetoid = decSetoid _≟_
toℕ-double : ∀ x → toℕ (double x) ≡ 2 ℕ.* (toℕ x)
toℕ-double zero = refl
toℕ-double 1+[2 x ] = cong ((2 ℕ.*_) ∘ ℕ.suc) (toℕ-double x)
toℕ-double 2[1+ x ] = cong (2 ℕ.*_) (sym (ℕₚ.*-distribˡ-+ 2 1 (toℕ x)))
toℕ-suc : ∀ x → toℕ (suc x) ≡ ℕ.suc (toℕ x)
toℕ-suc zero = refl
toℕ-suc 2[1+ x ] = cong (ℕ.suc ∘ (2 ℕ.*_)) (toℕ-suc x)
toℕ-suc 1+[2 x ] = ℕₚ.*-distribˡ-+ 2 1 (toℕ x)
toℕ-pred : ∀ x → toℕ (pred x) ≡ ℕ.pred (toℕ x)
toℕ-pred zero = refl
toℕ-pred 2[1+ x ] = cong ℕ.pred $ sym $ ℕₚ.*-distribˡ-+ 2 1 (toℕ x)
toℕ-pred 1+[2 x ] = toℕ-double x
toℕ-fromℕ' : toℕ ∘ fromℕ' ≗ id
toℕ-fromℕ' 0 = refl
toℕ-fromℕ' (ℕ.suc n) = begin
toℕ (fromℕ' (ℕ.suc n)) ≡⟨⟩
toℕ (suc (fromℕ' n)) ≡⟨ toℕ-suc (fromℕ' n) ⟩
ℕ.suc (toℕ (fromℕ' n)) ≡⟨ cong ℕ.suc (toℕ-fromℕ' n) ⟩
ℕ.suc n ∎
where open ≡-Reasoning
fromℕ≡fromℕ' : fromℕ ≗ fromℕ'
fromℕ≡fromℕ' n = fromℕ-helper≡fromℕ' n n ℕₚ.≤-refl
where
split : ℕᵇ → Maybe Bool × ℕᵇ
split zero = nothing , zero
split 2[1+ n ] = just false , n
split 1+[2 n ] = just true , n
head = proj₁ ∘ split
tail = proj₂ ∘ split
split-injective : Injective _≡_ _≡_ split
split-injective {zero} {zero} refl = refl
split-injective {2[1+ _ ]} {2[1+ _ ]} refl = refl
split-injective {1+[2 _ ]} {1+[2 _ ]} refl = refl
split-if : ∀ x xs → split (if x then 1+[2 xs ] else 2[1+ xs ]) ≡ (just x , xs)
split-if false xs = refl
split-if true xs = refl
head-suc : ∀ n → head (suc (suc (suc n))) ≡ head (suc n)
head-suc zero = refl
head-suc 2[1+ n ] = refl
head-suc 1+[2 n ] = refl
tail-suc : ∀ n → suc (tail (suc n)) ≡ tail (suc (suc (suc n)))
tail-suc zero = refl
tail-suc 2[1+ n ] = refl
tail-suc 1+[2 n ] = refl
head-homo : ∀ n → head (suc (fromℕ' n)) ≡ just (n % 2 ℕ.≡ᵇ 0)
head-homo ℕ.zero = refl
head-homo (ℕ.suc ℕ.zero) = refl
head-homo (ℕ.suc (ℕ.suc n)) = trans (head-suc (fromℕ' n)) (head-homo n)
open ≡-Reasoning
tail-homo : ∀ n → tail (suc (fromℕ' n)) ≡ fromℕ' (n / 2)
tail-homo ℕ.zero = refl
tail-homo (ℕ.suc ℕ.zero) = refl
tail-homo (ℕ.suc (ℕ.suc n)) = begin
tail (suc (fromℕ' (ℕ.suc (ℕ.suc n)))) ≡˘⟨ tail-suc (fromℕ' n) ⟩
suc (tail (suc (fromℕ' n))) ≡⟨ cong suc (tail-homo n) ⟩
fromℕ' (ℕ.suc (n / 2)) ≡˘⟨ cong fromℕ' (+-distrib-/-∣ˡ {2} n ∣-refl) ⟩
fromℕ' (ℕ.suc (ℕ.suc n) / 2) ∎
fromℕ-helper≡fromℕ' : ∀ n w → n ℕ.≤ w → fromℕ.helper n n w ≡ fromℕ' n
fromℕ-helper≡fromℕ' ℕ.zero w p = refl
fromℕ-helper≡fromℕ' (ℕ.suc n) (ℕ.suc w) (s≤s n≤w) =
split-injective (begin
split (fromℕ.helper n (ℕ.suc n) (ℕ.suc w)) ≡⟨ split-if _ _ ⟩
just (n % 2 ℕ.≡ᵇ 0) , fromℕ.helper n (n / 2) w ≡⟨ cong (_ ,_) rec-n/2 ⟩
just (n % 2 ℕ.≡ᵇ 0) , fromℕ' (n / 2) ≡˘⟨ cong₂ _,_ (head-homo n) (tail-homo n) ⟩
head (fromℕ' (ℕ.suc n)) , tail (fromℕ' (ℕ.suc n)) ≡⟨⟩
split (fromℕ' (ℕ.suc n)) ∎)
where rec-n/2 = fromℕ-helper≡fromℕ' (n / 2) w (ℕₚ.≤-trans (m/n≤m n 2) n≤w)
toℕ-fromℕ : toℕ ∘ fromℕ ≗ id
toℕ-fromℕ n rewrite fromℕ≡fromℕ' n = toℕ-fromℕ' n
toℕ-injective : Injective _≡_ _≡_ toℕ
toℕ-injective {zero} {zero} _ = refl
toℕ-injective {2[1+ x ]} {2[1+ y ]} 2[1+xN]≡2[1+yN] = cong 2[1+_] x≡y
where
1+xN≡1+yN = ℕₚ.*-cancelˡ-≡ {ℕ.suc _} {ℕ.suc _} 1 2[1+xN]≡2[1+yN]
xN≡yN = cong ℕ.pred 1+xN≡1+yN
x≡y = toℕ-injective xN≡yN
toℕ-injective {2[1+ x ]} {1+[2 y ]} 2[1+xN]≡1+2yN =
contradiction 2[1+xN]≡1+2yN (ℕₚ.even≢odd (ℕ.suc (toℕ x)) (toℕ y))
toℕ-injective {1+[2 x ]} {2[1+ y ]} 1+2xN≡2[1+yN] =
contradiction (sym 1+2xN≡2[1+yN]) (ℕₚ.even≢odd (ℕ.suc (toℕ y)) (toℕ x))
toℕ-injective {1+[2 x ]} {1+[2 y ]} 1+2xN≡1+2yN = cong 1+[2_] x≡y
where
2xN≡2yN = cong ℕ.pred 1+2xN≡1+2yN
xN≡yN = ℕₚ.*-cancelˡ-≡ 1 2xN≡2yN
x≡y = toℕ-injective xN≡yN
toℕ-surjective : Surjective _≡_ toℕ
toℕ-surjective n = (fromℕ n , toℕ-fromℕ n)
toℕ-isRelHomomorphism : IsRelHomomorphism _≡_ _≡_ toℕ
toℕ-isRelHomomorphism = record
{ cong = cong toℕ
}
fromℕ-injective : Injective _≡_ _≡_ fromℕ
fromℕ-injective {x} {y} f[x]≡f[y] = begin
x ≡⟨ sym (toℕ-fromℕ x) ⟩
toℕ (fromℕ x) ≡⟨ cong toℕ f[x]≡f[y] ⟩
toℕ (fromℕ y) ≡⟨ toℕ-fromℕ y ⟩
y ∎
where open ≡-Reasoning
fromℕ-toℕ : fromℕ ∘ toℕ ≗ id
fromℕ-toℕ = toℕ-injective ∘ toℕ-fromℕ ∘ toℕ
fromℕ-pred : ∀ n → fromℕ (ℕ.pred n) ≡ pred (fromℕ n)
fromℕ-pred n = begin
fromℕ (ℕ.pred n) ≡⟨ cong (fromℕ ∘ ℕ.pred) (sym (toℕ-fromℕ n)) ⟩
fromℕ (ℕ.pred (toℕ x)) ≡⟨ cong fromℕ (sym (toℕ-pred x)) ⟩
fromℕ (toℕ (pred x)) ≡⟨ fromℕ-toℕ (pred x) ⟩
pred x ≡⟨ refl ⟩
pred (fromℕ n) ∎
where open ≡-Reasoning; x = fromℕ n
x≡0⇒toℕ[x]≡0 : ∀ {x} → x ≡ zero → toℕ x ≡ 0
x≡0⇒toℕ[x]≡0 {zero} _ = refl
toℕ[x]≡0⇒x≡0 : ∀ {x} → toℕ x ≡ 0 → x ≡ zero
toℕ[x]≡0⇒x≡0 {zero} _ = refl
x≮0 : ∀ {x} → x ≮ zero
x≮0 ()
x≢0⇒x>0 : ∀ {x} → x ≢ zero → x > zero
x≢0⇒x>0 {zero} 0≢0 = contradiction refl 0≢0
x≢0⇒x>0 {2[1+ _ ]} _ = 0<even
x≢0⇒x>0 {1+[2 _ ]} _ = 0<odd
1+[2x]<2[1+x] : ∀ x → 1+[2 x ] < 2[1+ x ]
1+[2x]<2[1+x] x = odd<even (inj₂ refl)
<⇒≢ : _<_ ⇒ _≢_
<⇒≢ (even<even x<x) refl = <⇒≢ x<x refl
<⇒≢ (odd<odd x<x) refl = <⇒≢ x<x refl
>⇒≢ : _>_ ⇒ _≢_
>⇒≢ y<x = ≢-sym (<⇒≢ y<x)
≡⇒≮ : _≡_ ⇒ _≮_
≡⇒≮ x≡y x<y = <⇒≢ x<y x≡y
≡⇒≯ : _≡_ ⇒ _≯_
≡⇒≯ x≡y x>y = >⇒≢ x>y x≡y
<⇒≯ : _<_ ⇒ _≯_
<⇒≯ (even<even x<y) (even<even y<x) = <⇒≯ x<y y<x
<⇒≯ (even<odd x<y) (odd<even (inj₁ y<x)) = <⇒≯ x<y y<x
<⇒≯ (even<odd x<y) (odd<even (inj₂ refl)) = <⇒≢ x<y refl
<⇒≯ (odd<even (inj₁ x<y)) (even<odd y<x) = <⇒≯ x<y y<x
<⇒≯ (odd<even (inj₂ refl)) (even<odd y<x) = <⇒≢ y<x refl
<⇒≯ (odd<odd x<y) (odd<odd y<x) = <⇒≯ x<y y<x
>⇒≮ : _>_ ⇒ _≮_
>⇒≮ y<x = <⇒≯ y<x
<⇒≤ : _<_ ⇒ _≤_
<⇒≤ = inj₁
toℕ-mono-< : toℕ Preserves _<_ ⟶ ℕ._<_
toℕ-mono-< {zero} {2[1+ _ ]} _ = ℕₚ.0<1+n
toℕ-mono-< {zero} {1+[2 _ ]} _ = ℕₚ.0<1+n
toℕ-mono-< {2[1+ x ]} {2[1+ y ]} (even<even x<y) = begin
ℕ.suc (2 ℕ.* (ℕ.suc xN)) ≤⟨ ℕₚ.+-monoʳ-≤ 1 (ℕₚ.*-monoʳ-≤ 2 xN<yN) ⟩
ℕ.suc (2 ℕ.* yN) ≤⟨ ℕₚ.≤-step ℕₚ.≤-refl ⟩
2 ℕ.+ (2 ℕ.* yN) ≡⟨ sym (ℕₚ.*-distribˡ-+ 2 1 yN) ⟩
2 ℕ.* (ℕ.suc yN) ∎
where open ℕₚ.≤-Reasoning; xN = toℕ x; yN = toℕ y; xN<yN = toℕ-mono-< x<y
toℕ-mono-< {2[1+ x ]} {1+[2 y ]} (even<odd x<y) =
ℕₚ.+-monoʳ-≤ 1 (ℕₚ.*-monoʳ-≤ 2 (toℕ-mono-< x<y))
toℕ-mono-< {1+[2 x ]} {2[1+ y ]} (odd<even (inj₁ x<y)) = begin
ℕ.suc (ℕ.suc (2 ℕ.* xN)) ≡⟨⟩
2 ℕ.+ (2 ℕ.* xN) ≡⟨ sym (ℕₚ.*-distribˡ-+ 2 1 xN) ⟩
2 ℕ.* (ℕ.suc xN) ≤⟨ ℕₚ.*-monoʳ-≤ 2 xN<yN ⟩
2 ℕ.* yN ≤⟨ ℕₚ.*-monoʳ-≤ 2 (ℕₚ.≤-step ℕₚ.≤-refl) ⟩
2 ℕ.* (ℕ.suc yN) ∎
where open ℕₚ.≤-Reasoning; xN = toℕ x; yN = toℕ y; xN<yN = toℕ-mono-< x<y
toℕ-mono-< {1+[2 x ]} {2[1+ .x ]} (odd<even (inj₂ refl)) =
ℕₚ.≤-reflexive (sym (ℕₚ.*-distribˡ-+ 2 1 (toℕ x)))
toℕ-mono-< {1+[2 x ]} {1+[2 y ]} (odd<odd x<y) = ℕₚ.+-monoʳ-< 1 (ℕₚ.*-monoʳ-< 1 xN<yN)
where xN = toℕ x; yN = toℕ y; xN<yN = toℕ-mono-< x<y
toℕ-cancel-< : ∀ {x y} → toℕ x ℕ.< toℕ y → x < y
toℕ-cancel-< {zero} {2[1+ y ]} x<y = 0<even
toℕ-cancel-< {zero} {1+[2 y ]} x<y = 0<odd
toℕ-cancel-< {2[1+ x ]} {2[1+ y ]} x<y =
even<even (toℕ-cancel-< (ℕ.≤-pred (ℕₚ.*-cancelˡ-< 2 x<y)))
toℕ-cancel-< {2[1+ x ]} {1+[2 y ]} x<y
rewrite ℕₚ.*-distribˡ-+ 2 1 (toℕ x) =
even<odd (toℕ-cancel-< (ℕₚ.*-cancelˡ-< 2 (ℕₚ.≤-trans (s≤s (ℕₚ.n≤1+n _)) (ℕₚ.≤-pred x<y))))
toℕ-cancel-< {1+[2 x ]} {2[1+ y ]} x<y with toℕ x ℕₚ.≟ toℕ y
... | yes x≡y = odd<even (inj₂ (toℕ-injective x≡y))
... | no x≢y
rewrite ℕₚ.+-suc (toℕ y) (toℕ y ℕ.+ 0) =
odd<even (inj₁ (toℕ-cancel-< (ℕₚ.≤∧≢⇒< (ℕₚ.*-cancelˡ-≤ 1 (ℕₚ.+-cancelˡ-≤ 2 x<y)) x≢y)))
toℕ-cancel-< {1+[2 x ]} {1+[2 y ]} x<y =
odd<odd (toℕ-cancel-< (ℕₚ.*-cancelˡ-< 2 (ℕ.≤-pred x<y)))
fromℕ-cancel-< : ∀ {x y} → fromℕ x < fromℕ y → x ℕ.< y
fromℕ-cancel-< = subst₂ ℕ._<_ (toℕ-fromℕ _) (toℕ-fromℕ _) ∘ toℕ-mono-<
fromℕ-mono-< : fromℕ Preserves ℕ._<_ ⟶ _<_
fromℕ-mono-< = toℕ-cancel-< ∘ subst₂ ℕ._<_ (sym (toℕ-fromℕ _)) (sym (toℕ-fromℕ _))
toℕ-isHomomorphism-< : IsOrderHomomorphism _≡_ _≡_ _<_ ℕ._<_ toℕ
toℕ-isHomomorphism-< = record
{ cong = cong toℕ
; mono = toℕ-mono-<
}
toℕ-isMonomorphism-< : IsOrderMonomorphism _≡_ _≡_ _<_ ℕ._<_ toℕ
toℕ-isMonomorphism-< = record
{ isOrderHomomorphism = toℕ-isHomomorphism-<
; injective = toℕ-injective
; cancel = toℕ-cancel-<
}
<-irrefl : Irreflexive _≡_ _<_
<-irrefl refl (even<even x<x) = <-irrefl refl x<x
<-irrefl refl (odd<odd x<x) = <-irrefl refl x<x
<-trans : Transitive _<_
<-trans {zero} {_} {2[1+ _ ]} _ _ = 0<even
<-trans {zero} {_} {1+[2 _ ]} _ _ = 0<odd
<-trans (even<even x<y) (even<even y<z) = even<even (<-trans x<y y<z)
<-trans (even<even x<y) (even<odd y<z) = even<odd (<-trans x<y y<z)
<-trans (even<odd x<y) (odd<even (inj₁ y<z)) = even<even (<-trans x<y y<z)
<-trans (even<odd x<y) (odd<even (inj₂ refl)) = even<even x<y
<-trans (even<odd x<y) (odd<odd y<z) = even<odd (<-trans x<y y<z)
<-trans (odd<even (inj₁ x<y)) (even<even y<z) = odd<even (inj₁ (<-trans x<y y<z))
<-trans (odd<even (inj₂ refl)) (even<even x<z) = odd<even (inj₁ x<z)
<-trans (odd<even (inj₁ x<y)) (even<odd y<z) = odd<odd (<-trans x<y y<z)
<-trans (odd<even (inj₂ refl)) (even<odd x<z) = odd<odd x<z
<-trans (odd<odd x<y) (odd<even (inj₁ y<z)) = odd<even (inj₁ (<-trans x<y y<z))
<-trans (odd<odd x<y) (odd<even (inj₂ refl)) = odd<even (inj₁ x<y)
<-trans (odd<odd x<y) (odd<odd y<z) = odd<odd (<-trans x<y y<z)
<-cmp : Trichotomous _≡_ _<_
<-cmp zero zero = tri≈ x≮0 refl x≮0
<-cmp zero 2[1+ _ ] = tri< 0<even (λ()) x≮0
<-cmp zero 1+[2 _ ] = tri< 0<odd (λ()) x≮0
<-cmp 2[1+ _ ] zero = tri> (λ()) (λ()) 0<even
<-cmp 2[1+ x ] 2[1+ y ] with <-cmp x y
... | tri< x<y _ _ = tri< lt (<⇒≢ lt) (<⇒≯ lt) where lt = even<even x<y
... | tri≈ _ refl _ = tri≈ (<-irrefl refl) refl (<-irrefl refl)
... | tri> _ _ x>y = tri> (>⇒≮ gt) (>⇒≢ gt) gt where gt = even<even x>y
<-cmp 2[1+ x ] 1+[2 y ] with <-cmp x y
... | tri< x<y _ _ = tri< lt (<⇒≢ lt) (<⇒≯ lt) where lt = even<odd x<y
... | tri≈ _ refl _ = tri> (>⇒≮ gt) (>⇒≢ gt) gt
where
gt = subst (_< 2[1+ x ]) refl (1+[2x]<2[1+x] x)
... | tri> _ _ y<x = tri> (>⇒≮ gt) (>⇒≢ gt) gt where gt = odd<even (inj₁ y<x)
<-cmp 1+[2 _ ] zero = tri> (>⇒≮ gt) (>⇒≢ gt) gt where gt = 0<odd
<-cmp 1+[2 x ] 2[1+ y ] with <-cmp x y
... | tri< x<y _ _ = tri< lt (<⇒≢ lt) (<⇒≯ lt) where lt = odd<even (inj₁ x<y)
... | tri≈ _ x≡y _ = tri< lt (<⇒≢ lt) (<⇒≯ lt) where lt = odd<even (inj₂ x≡y)
... | tri> _ _ x>y = tri> (>⇒≮ gt) (>⇒≢ gt) gt where gt = even<odd x>y
<-cmp 1+[2 x ] 1+[2 y ] with <-cmp x y
... | tri< x<y _ _ = tri< lt (<⇒≢ lt) (<⇒≯ lt) where lt = odd<odd x<y
... | tri≈ _ refl _ = tri≈ (≡⇒≮ refl) refl (≡⇒≯ refl)
... | tri> _ _ x>y = tri> (>⇒≮ gt) (>⇒≢ gt) gt where gt = odd<odd x>y
_<?_ : Decidable _<_
_<?_ = tri⇒dec< <-cmp
<-isStrictPartialOrder : IsStrictPartialOrder _≡_ _<_
<-isStrictPartialOrder = record
{ isEquivalence = isEquivalence
; irrefl = <-irrefl
; trans = <-trans
; <-resp-≈ = resp₂ _<_
}
<-isStrictTotalOrder : IsStrictTotalOrder _≡_ _<_
<-isStrictTotalOrder = record
{ isEquivalence = isEquivalence
; trans = <-trans
; compare = <-cmp
}
<-strictPartialOrder : StrictPartialOrder _ _ _
<-strictPartialOrder = record
{ isStrictPartialOrder = <-isStrictPartialOrder
}
<-strictTotalOrder : StrictTotalOrder _ _ _
<-strictTotalOrder = record
{ isStrictTotalOrder = <-isStrictTotalOrder
}
x<2[1+x] : ∀ x → x < 2[1+ x ]
x<1+[2x] : ∀ x → x < 1+[2 x ]
x<2[1+x] zero = 0<even
x<2[1+x] 2[1+ x ] = even<even (x<2[1+x] x)
x<2[1+x] 1+[2 x ] = odd<even (inj₁ (x<1+[2x] x))
x<1+[2x] zero = 0<odd
x<1+[2x] 2[1+ x ] = even<odd (x<2[1+x] x)
x<1+[2x] 1+[2 x ] = odd<odd (x<1+[2x] x)
<⇒≱ : _<_ ⇒ _≱_
<⇒≱ x<y (inj₁ y<x) = contradiction y<x (<⇒≯ x<y)
<⇒≱ x<y (inj₂ y≡x) = contradiction (sym y≡x) (<⇒≢ x<y)
≤⇒≯ : _≤_ ⇒ _≯_
≤⇒≯ x≤y x>y = <⇒≱ x>y x≤y
≮⇒≥ : _≮_ ⇒ _≥_
≮⇒≥ {x} {y} x≮y with <-cmp x y
... | tri< lt _ _ = contradiction lt x≮y
... | tri≈ _ eq _ = inj₂ (sym eq)
... | tri> _ _ y<x = <⇒≤ y<x
≰⇒> : _≰_ ⇒ _>_
≰⇒> {x} {y} x≰y with <-cmp x y
... | tri< lt _ _ = contradiction (<⇒≤ lt) x≰y
... | tri≈ _ eq _ = contradiction (inj₂ eq) x≰y
... | tri> _ _ x>y = x>y
≤∧≢⇒< : ∀ {x y} → x ≤ y → x ≢ y → x < y
≤∧≢⇒< (inj₁ x<y) _ = x<y
≤∧≢⇒< (inj₂ x≡y) x≢y = contradiction x≡y x≢y
0≤x : ∀ x → zero ≤ x
0≤x zero = inj₂ refl
0≤x 2[1+ _ ] = inj₁ 0<even
0≤x 1+[2 x ] = inj₁ 0<odd
x≤0⇒x≡0 : ∀ {x} → x ≤ zero → x ≡ zero
x≤0⇒x≡0 (inj₂ x≡0) = x≡0
fromℕ-mono-≤ : fromℕ Preserves ℕ._≤_ ⟶ _≤_
fromℕ-mono-≤ m≤n with ℕₚ.m≤n⇒m<n∨m≡n m≤n
... | inj₁ m<n = inj₁ (fromℕ-mono-< m<n)
... | inj₂ m≡n = inj₂ (cong fromℕ m≡n)
toℕ-mono-≤ : toℕ Preserves _≤_ ⟶ ℕ._≤_
toℕ-mono-≤ (inj₁ x<y) = ℕₚ.<⇒≤ (toℕ-mono-< x<y)
toℕ-mono-≤ (inj₂ refl) = ℕₚ.≤-reflexive refl
toℕ-cancel-≤ : ∀ {x y} → toℕ x ℕ.≤ toℕ y → x ≤ y
toℕ-cancel-≤ = subst₂ _≤_ (fromℕ-toℕ _) (fromℕ-toℕ _) ∘ fromℕ-mono-≤
fromℕ-cancel-≤ : ∀ {x y} → fromℕ x ≤ fromℕ y → x ℕ.≤ y
fromℕ-cancel-≤ = subst₂ ℕ._≤_ (toℕ-fromℕ _) (toℕ-fromℕ _) ∘ toℕ-mono-≤
toℕ-isHomomorphism-≤ : IsOrderHomomorphism _≡_ _≡_ _≤_ ℕ._≤_ toℕ
toℕ-isHomomorphism-≤ = record
{ cong = cong toℕ
; mono = toℕ-mono-≤
}
toℕ-isMonomorphism-≤ : IsOrderMonomorphism _≡_ _≡_ _≤_ ℕ._≤_ toℕ
toℕ-isMonomorphism-≤ = record
{ isOrderHomomorphism = toℕ-isHomomorphism-≤
; injective = toℕ-injective
; cancel = toℕ-cancel-≤
}
≤-refl : Reflexive _≤_
≤-refl = inj₂ refl
≤-reflexive : _≡_ ⇒ _≤_
≤-reflexive {x} {_} refl = ≤-refl {x}
≤-trans : Transitive _≤_
≤-trans = StrictToNonStrict.trans isEquivalence (resp₂ _<_) <-trans
<-≤-trans : ∀ {x y z} → x < y → y ≤ z → x < z
<-≤-trans x<y (inj₁ y<z) = <-trans x<y y<z
<-≤-trans x<y (inj₂ refl) = x<y
≤-<-trans : ∀ {x y z} → x ≤ y → y < z → x < z
≤-<-trans (inj₁ x<y) y<z = <-trans x<y y<z
≤-<-trans (inj₂ refl) y<z = y<z
≤-antisym : Antisymmetric _≡_ _≤_
≤-antisym = StrictToNonStrict.antisym isEquivalence <-trans <-irrefl
≤-total : Total _≤_
≤-total x y with <-cmp x y
... | tri< x<y _ _ = inj₁ (<⇒≤ x<y)
... | tri≈ _ x≡y _ = inj₁ (≤-reflexive x≡y)
... | tri> _ _ y<x = inj₂ (<⇒≤ y<x)
_≤?_ : Decidable _≤_
x ≤? y with <-cmp x y
... | tri< x<y _ _ = yes (<⇒≤ x<y)
... | tri≈ _ x≡y _ = yes (≤-reflexive x≡y)
... | tri> _ _ y<x = no (<⇒≱ y<x)
≤-isPreorder : IsPreorder _≡_ _≤_
≤-isPreorder = record
{ isEquivalence = isEquivalence
; reflexive = ≤-reflexive
; trans = ≤-trans
}
≤-isPartialOrder : IsPartialOrder _≡_ _≤_
≤-isPartialOrder = record
{ isPreorder = ≤-isPreorder
; antisym = ≤-antisym
}
≤-isTotalOrder : IsTotalOrder _≡_ _≤_
≤-isTotalOrder = record
{ isPartialOrder = ≤-isPartialOrder
; total = ≤-total
}
≤-isDecTotalOrder : IsDecTotalOrder _≡_ _≤_
≤-isDecTotalOrder = record
{ isTotalOrder = ≤-isTotalOrder
; _≟_ = _≟_
; _≤?_ = _≤?_
}
≤-preorder : Preorder 0ℓ 0ℓ 0ℓ
≤-preorder = record
{ isPreorder = ≤-isPreorder
}
≤-partialOrder : Poset 0ℓ 0ℓ 0ℓ
≤-partialOrder = record
{ isPartialOrder = ≤-isPartialOrder
}
≤-totalOrder : TotalOrder 0ℓ 0ℓ 0ℓ
≤-totalOrder = record
{ isTotalOrder = ≤-isTotalOrder
}
≤-decTotalOrder : DecTotalOrder 0ℓ 0ℓ 0ℓ
≤-decTotalOrder = record
{ isDecTotalOrder = ≤-isDecTotalOrder
}
module ≤-Reasoning = InequalityReasoning
≤-isPreorder
<-trans
(resp₂ _<_) <⇒≤
<-≤-trans ≤-<-trans
hiding (step-≈; step-≈˘)
<⇒<ℕ : ∀ {x y} → x < y → x <ℕ y
<⇒<ℕ x<y = toℕ-mono-< x<y
<ℕ⇒< : ∀ {x y} → x <ℕ y → x < y
<ℕ⇒< {x} {y} t[x]<t[y] = begin-strict
x ≡⟨ sym (fromℕ-toℕ x) ⟩
fromℕ (toℕ x) <⟨ fromℕ-mono-< t[x]<t[y] ⟩
fromℕ (toℕ y) ≡⟨ fromℕ-toℕ y ⟩
y ∎
where open ≤-Reasoning
+-rawMagma : RawMagma 0ℓ 0ℓ
+-rawMagma = record
{ _≈_ = _≡_
; _∙_ = _+_
}
+-0-rawMonoid : RawMonoid 0ℓ 0ℓ
+-0-rawMonoid = record
{ _≈_ = _≡_
; _∙_ = _+_
; ε = 0ᵇ
}
toℕ-homo-+ : ∀ x y → toℕ (x + y) ≡ toℕ x ℕ.+ toℕ y
toℕ-homo-+ zero _ = refl
toℕ-homo-+ 2[1+ x ] zero = cong ℕ.suc (sym (ℕₚ.+-identityʳ _))
toℕ-homo-+ 1+[2 x ] zero = cong ℕ.suc (sym (ℕₚ.+-identityʳ _))
toℕ-homo-+ 2[1+ x ] 2[1+ y ] = begin
toℕ (2[1+ x ] + 2[1+ y ]) ≡⟨⟩
toℕ 2[1+ (suc (x + y)) ] ≡⟨⟩
2 ℕ.* (1 ℕ.+ (toℕ (suc (x + y)))) ≡⟨ cong ((2 ℕ.*_) ∘ ℕ.suc) (toℕ-suc (x + y)) ⟩
2 ℕ.* (2 ℕ.+ toℕ (x + y)) ≡⟨ cong ((2 ℕ.*_) ∘ (2 ℕ.+_)) (toℕ-homo-+ x y) ⟩
2 ℕ.* (2 ℕ.+ (toℕ x ℕ.+ toℕ y)) ≡⟨ solve 2 (λ m n → con 2 :* (con 2 :+ (m :+ n)) :=
con 2 :* (con 1 :+ m) :+ con 2 :* (con 1 :+ n))
refl (toℕ x) (toℕ y) ⟩
toℕ 2[1+ x ] ℕ.+ toℕ 2[1+ y ] ∎
where open ≡-Reasoning
toℕ-homo-+ 2[1+ x ] 1+[2 y ] = begin
toℕ (2[1+ x ] + 1+[2 y ]) ≡⟨⟩
toℕ (suc 2[1+ (x + y) ]) ≡⟨ toℕ-suc 2[1+ (x + y) ] ⟩
ℕ.suc (toℕ 2[1+ (x + y) ]) ≡⟨⟩
ℕ.suc (2 ℕ.* (ℕ.suc (toℕ (x + y)))) ≡⟨ cong (λ v → ℕ.suc (2 ℕ.* ℕ.suc v)) (toℕ-homo-+ x y) ⟩
ℕ.suc (2 ℕ.* (ℕ.suc (m ℕ.+ n))) ≡⟨ solve 2 (λ m n → con 1 :+ (con 2 :* (con 1 :+ (m :+ n))) :=
con 2 :* (con 1 :+ m) :+ (con 1 :+ (con 2 :* n)))
refl m n ⟩
(2 ℕ.* ℕ.suc m) ℕ.+ (ℕ.suc (2 ℕ.* n)) ≡⟨⟩
toℕ 2[1+ x ] ℕ.+ toℕ 1+[2 y ] ∎
where open ≡-Reasoning; m = toℕ x; n = toℕ y
toℕ-homo-+ 1+[2 x ] 2[1+ y ] = begin
toℕ (1+[2 x ] + 2[1+ y ]) ≡⟨⟩
toℕ (suc 2[1+ (x + y) ]) ≡⟨ toℕ-suc 2[1+ (x + y) ] ⟩
ℕ.suc (toℕ 2[1+ (x + y) ]) ≡⟨⟩
ℕ.suc (2 ℕ.* (ℕ.suc (toℕ (x + y)))) ≡⟨ cong (ℕ.suc ∘ (2 ℕ.*_) ∘ ℕ.suc) (toℕ-homo-+ x y) ⟩
ℕ.suc (2 ℕ.* (ℕ.suc (m ℕ.+ n))) ≡⟨ solve 2 (λ m n → con 1 :+ (con 2 :* (con 1 :+ (m :+ n))) :=
(con 1 :+ (con 2 :* m)) :+ (con 2 :* (con 1 :+ n)))
refl m n ⟩
(ℕ.suc (2 ℕ.* m)) ℕ.+ (2 ℕ.* (ℕ.suc n)) ≡⟨⟩
toℕ 1+[2 x ] ℕ.+ toℕ 2[1+ y ] ∎
where open ≡-Reasoning; m = toℕ x; n = toℕ y
toℕ-homo-+ 1+[2 x ] 1+[2 y ] = begin
toℕ (1+[2 x ] + 1+[2 y ]) ≡⟨⟩
toℕ (suc 1+[2 (x + y) ]) ≡⟨ toℕ-suc 1+[2 (x + y) ] ⟩
ℕ.suc (toℕ 1+[2 (x + y) ]) ≡⟨⟩
ℕ.suc (ℕ.suc (2 ℕ.* (toℕ (x + y)))) ≡⟨ cong (ℕ.suc ∘ ℕ.suc ∘ (2 ℕ.*_)) (toℕ-homo-+ x y) ⟩
ℕ.suc (ℕ.suc (2 ℕ.* (m ℕ.+ n))) ≡⟨ solve 2 (λ m n → con 1 :+ (con 1 :+ (con 2 :* (m :+ n))) :=
(con 1 :+ (con 2 :* m)) :+ (con 1 :+ (con 2 :* n)))
refl m n ⟩
(ℕ.suc (2 ℕ.* m)) ℕ.+ (ℕ.suc (2 ℕ.* n)) ≡⟨⟩
toℕ 1+[2 x ] ℕ.+ toℕ 1+[2 y ] ∎
where open ≡-Reasoning; m = toℕ x; n = toℕ y
toℕ-isMagmaHomomorphism-+ : IsMagmaHomomorphism +-rawMagma ℕₚ.+-rawMagma toℕ
toℕ-isMagmaHomomorphism-+ = record
{ isRelHomomorphism = toℕ-isRelHomomorphism
; homo = toℕ-homo-+
}
toℕ-isMonoidHomomorphism-+ : IsMonoidHomomorphism +-0-rawMonoid ℕₚ.+-0-rawMonoid toℕ
toℕ-isMonoidHomomorphism-+ = record
{ isMagmaHomomorphism = toℕ-isMagmaHomomorphism-+
; ε-homo = refl
}
toℕ-isMonoidMonomorphism-+ : IsMonoidMonomorphism +-0-rawMonoid ℕₚ.+-0-rawMonoid toℕ
toℕ-isMonoidMonomorphism-+ = record
{ isMonoidHomomorphism = toℕ-isMonoidHomomorphism-+
; injective = toℕ-injective
}
suc≗1+ : suc ≗ 1ᵇ +_
suc≗1+ zero = refl
suc≗1+ 2[1+ _ ] = refl
suc≗1+ 1+[2 _ ] = refl
suc-+ : ∀ x y → suc x + y ≡ suc (x + y)
suc-+ zero y = sym (suc≗1+ y)
suc-+ 2[1+ x ] zero = refl
suc-+ 1+[2 x ] zero = refl
suc-+ 2[1+ x ] 2[1+ y ] = cong (suc ∘ 2[1+_]) (suc-+ x y)
suc-+ 2[1+ x ] 1+[2 y ] = cong (suc ∘ 1+[2_]) (suc-+ x y)
suc-+ 1+[2 x ] 2[1+ y ] = refl
suc-+ 1+[2 x ] 1+[2 y ] = refl
1+≗suc : (1ᵇ +_) ≗ suc
1+≗suc = suc-+ zero
fromℕ'-homo-+ : ∀ m n → fromℕ' (m ℕ.+ n) ≡ fromℕ' m + fromℕ' n
fromℕ'-homo-+ 0 _ = refl
fromℕ'-homo-+ (ℕ.suc m) n = begin
fromℕ' ((ℕ.suc m) ℕ.+ n) ≡⟨⟩
suc (fromℕ' (m ℕ.+ n)) ≡⟨ cong suc (fromℕ'-homo-+ m n) ⟩
suc (a + b) ≡⟨ sym (suc-+ a b) ⟩
(suc a) + b ≡⟨⟩
(fromℕ' (ℕ.suc m)) + (fromℕ' n) ∎
where open ≡-Reasoning; a = fromℕ' m; b = fromℕ' n
fromℕ-homo-+ : ∀ m n → fromℕ (m ℕ.+ n) ≡ fromℕ m + fromℕ n
fromℕ-homo-+ m n rewrite fromℕ≡fromℕ' (m ℕ.+ n) | fromℕ≡fromℕ' m | fromℕ≡fromℕ' n =
fromℕ'-homo-+ m n
private
module +-Monomorphism = MonoidMonomorphism toℕ-isMonoidMonomorphism-+
+-assoc : Associative _+_
+-assoc = +-Monomorphism.assoc ℕₚ.+-isMagma ℕₚ.+-assoc
+-comm : Commutative _+_
+-comm = +-Monomorphism.comm ℕₚ.+-isMagma ℕₚ.+-comm
+-identityˡ : LeftIdentity zero _+_
+-identityˡ _ = refl
+-identityʳ : RightIdentity zero _+_
+-identityʳ = +-Monomorphism.identityʳ ℕₚ.+-isMagma ℕₚ.+-identityʳ
+-identity : Identity zero _+_
+-identity = +-identityˡ , +-identityʳ
+-cancelˡ-≡ : LeftCancellative _+_
+-cancelˡ-≡ = +-Monomorphism.cancelˡ ℕₚ.+-isMagma ℕₚ.+-cancelˡ-≡
+-cancelʳ-≡ : RightCancellative _+_
+-cancelʳ-≡ = +-Monomorphism.cancelʳ ℕₚ.+-isMagma ℕₚ.+-cancelʳ-≡
+-isMagma : IsMagma _+_
+-isMagma = isMagma _+_
+-isSemigroup : IsSemigroup _+_
+-isSemigroup = +-Monomorphism.isSemigroup ℕₚ.+-isSemigroup
+-isCommutativeSemigroup : IsCommutativeSemigroup _+_
+-isCommutativeSemigroup = record
{ isSemigroup = +-isSemigroup
; comm = +-comm
}
+-0-isMonoid : IsMonoid _+_ 0ᵇ
+-0-isMonoid = +-Monomorphism.isMonoid ℕₚ.+-0-isMonoid
+-0-isCommutativeMonoid : IsCommutativeMonoid _+_ 0ᵇ
+-0-isCommutativeMonoid = +-Monomorphism.isCommutativeMonoid ℕₚ.+-0-isCommutativeMonoid
+-magma : Magma 0ℓ 0ℓ
+-magma = magma _+_
+-semigroup : Semigroup 0ℓ 0ℓ
+-semigroup = record
{ isSemigroup = +-isSemigroup
}
+-commutativeSemigroup : CommutativeSemigroup 0ℓ 0ℓ
+-commutativeSemigroup = record
{ isCommutativeSemigroup = +-isCommutativeSemigroup
}
+-0-monoid : Monoid 0ℓ 0ℓ
+-0-monoid = record
{ ε = zero
; isMonoid = +-0-isMonoid
}
+-0-commutativeMonoid : CommutativeMonoid 0ℓ 0ℓ
+-0-commutativeMonoid = record
{ isCommutativeMonoid = +-0-isCommutativeMonoid
}
module Bin+CSemigroup = CommSemigProp +-commutativeSemigroup
+-mono-≤ : _+_ Preserves₂ _≤_ ⟶ _≤_ ⟶ _≤_
+-mono-≤ {x} {x′} {y} {y′} x≤x′ y≤y′ = begin
x + y ≡⟨ sym $ cong₂ _+_ (fromℕ-toℕ x) (fromℕ-toℕ y) ⟩
fromℕ m + fromℕ n ≡⟨ sym (fromℕ-homo-+ m n) ⟩
fromℕ (m ℕ.+ n) ≤⟨ fromℕ-mono-≤ (ℕₚ.+-mono-≤ m≤m′ n≤n′) ⟩
fromℕ (m′ ℕ.+ n′) ≡⟨ fromℕ-homo-+ m′ n′ ⟩
fromℕ m′ + fromℕ n′ ≡⟨ cong₂ _+_ (fromℕ-toℕ x′) (fromℕ-toℕ y′) ⟩
x′ + y′ ∎
where
open ≤-Reasoning
m = toℕ x; m′ = toℕ x′
n = toℕ y; n′ = toℕ y′
m≤m′ = toℕ-mono-≤ x≤x′; n≤n′ = toℕ-mono-≤ y≤y′
+-monoˡ-≤ : ∀ x → (_+ x) Preserves _≤_ ⟶ _≤_
+-monoˡ-≤ x y≤z = +-mono-≤ y≤z (≤-refl {x})
+-monoʳ-≤ : ∀ x → (x +_) Preserves _≤_ ⟶ _≤_
+-monoʳ-≤ x y≤z = +-mono-≤ (≤-refl {x}) y≤z
+-mono-<-≤ : _+_ Preserves₂ _<_ ⟶ _≤_ ⟶ _<_
+-mono-<-≤ {x} {x′} {y} {y′} x<x′ y≤y′ = begin-strict
x + y ≡⟨ sym $ cong₂ _+_ (fromℕ-toℕ x) (fromℕ-toℕ y) ⟩
fromℕ m + fromℕ n ≡⟨ sym (fromℕ-homo-+ m n) ⟩
fromℕ (m ℕ.+ n) <⟨ fromℕ-mono-< (ℕₚ.+-mono-<-≤ m<m′ n≤n′) ⟩
fromℕ (m′ ℕ.+ n′) ≡⟨ fromℕ-homo-+ m′ n′ ⟩
fromℕ m′ + fromℕ n′ ≡⟨ cong₂ _+_ (fromℕ-toℕ x′) (fromℕ-toℕ y′) ⟩
x′ + y′ ∎
where
open ≤-Reasoning
m = toℕ x; n = toℕ y
m′ = toℕ x′; n′ = toℕ y′
m<m′ = toℕ-mono-< x<x′; n≤n′ = toℕ-mono-≤ y≤y′
+-mono-≤-< : _+_ Preserves₂ _≤_ ⟶ _<_ ⟶ _<_
+-mono-≤-< {x} {x′} {y} {y′} x≤x′ y<y′ = subst₂ _<_ (+-comm y x) (+-comm y′ x′) y+x<y′+x′
where
y+x<y′+x′ = +-mono-<-≤ y<y′ x≤x′
+-monoˡ-< : ∀ x → (_+ x) Preserves _<_ ⟶ _<_
+-monoˡ-< x y<z = +-mono-<-≤ y<z (≤-refl {x})
+-monoʳ-< : ∀ x → (x +_) Preserves _<_ ⟶ _<_
+-monoʳ-< x y<z = +-mono-≤-< (≤-refl {x}) y<z
x≤y+x : ∀ x y → x ≤ y + x
x≤y+x x y = begin
x ≡⟨ sym (+-identityˡ x) ⟩
0ᵇ + x ≤⟨ +-monoˡ-≤ x (0≤x y) ⟩
y + x ∎
where open ≤-Reasoning
x≤x+y : ∀ x y → x ≤ x + y
x≤x+y x y = begin
x ≤⟨ x≤y+x x y ⟩
y + x ≡⟨ +-comm y x ⟩
x + y ∎
where open ≤-Reasoning
x<x+y : ∀ x {y} → y > 0ᵇ → x < x + y
x<x+y x {y} y>0 = begin-strict
x ≡⟨ sym (fromℕ-toℕ x) ⟩
fromℕ (toℕ x) <⟨ fromℕ-mono-< (ℕₚ.m<m+n (toℕ x) (toℕ-mono-< y>0)) ⟩
fromℕ (toℕ x ℕ.+ toℕ y) ≡⟨ fromℕ-homo-+ (toℕ x) (toℕ y) ⟩
fromℕ (toℕ x) + fromℕ (toℕ y) ≡⟨ cong₂ _+_ (fromℕ-toℕ x) (fromℕ-toℕ y) ⟩
x + y ∎
where open ≤-Reasoning
x<x+1 : ∀ x → x < x + 1ᵇ
x<x+1 x = x<x+y x 0<odd
x<1+x : ∀ x → x < 1ᵇ + x
x<1+x x rewrite +-comm 1ᵇ x = x<x+1 x
x<1⇒x≡0 : ∀ {x} → x < 1ᵇ → x ≡ zero
x<1⇒x≡0 0<odd = refl
x≢0⇒x+y≢0 : ∀ {x} (y : ℕᵇ) → x ≢ zero → x + y ≢ zero
x≢0⇒x+y≢0 {2[1+ _ ]} zero _ = λ()
x≢0⇒x+y≢0 {zero} _ 0≢0 = contradiction refl 0≢0
*-rawMagma : RawMagma 0ℓ 0ℓ
*-rawMagma = record
{ _≈_ = _≡_
; _∙_ = _*_
}
*-1-rawMonoid : RawMonoid 0ℓ 0ℓ
*-1-rawMonoid = record
{ _≈_ = _≡_
; _∙_ = _*_
; ε = 1ᵇ
}
private 2*ₙ2*ₙ = (2 ℕ.*_) ∘ (2 ℕ.*_)
toℕ-homo-* : ∀ x y → toℕ (x * y) ≡ toℕ x ℕ.* toℕ y
toℕ-homo-* x y = aux x y (size x ℕ.+ size y) ℕₚ.≤-refl
where
aux : (x y : ℕᵇ) → (cnt : ℕ) → (size x ℕ.+ size y ℕ.≤ cnt) → toℕ (x * y) ≡ toℕ x ℕ.* toℕ y
aux zero _ _ _ = refl
aux 2[1+ x ] zero _ _ = sym (ℕₚ.*-zeroʳ (toℕ x ℕ.+ (ℕ.suc (toℕ x ℕ.+ 0))))
aux 1+[2 x ] zero _ _ = sym (ℕₚ.*-zeroʳ (toℕ x ℕ.+ (toℕ x ℕ.+ 0)))
aux 2[1+ x ] 2[1+ y ] (ℕ.suc cnt) (s≤s |x|+1+|y|≤cnt) = begin
toℕ (2[1+ x ] * 2[1+ y ]) ≡⟨⟩
toℕ (double 2[1+ (x + (y + xy)) ]) ≡⟨ toℕ-double 2[1+ (x + (y + xy)) ] ⟩
2 ℕ.* (toℕ 2[1+ (x + (y + xy)) ]) ≡⟨⟩
2*ₙ2*ₙ (ℕ.suc (toℕ (x + (y + xy)))) ≡⟨ cong (2*ₙ2*ₙ ∘ ℕ.suc) (toℕ-homo-+ x (y + xy)) ⟩
2*ₙ2*ₙ (ℕ.suc (m ℕ.+ (toℕ (y + xy)))) ≡⟨ cong (2*ₙ2*ₙ ∘ ℕ.suc ∘ (m ℕ.+_)) (toℕ-homo-+ y xy) ⟩
2*ₙ2*ₙ (ℕ.suc (m ℕ.+ (n ℕ.+ toℕ xy))) ≡⟨ cong (2*ₙ2*ₙ ∘ ℕ.suc ∘ (m ℕ.+_) ∘ (n ℕ.+_))
(aux x y cnt |x|+|y|≤cnt) ⟩
2*ₙ2*ₙ (ℕ.suc (m ℕ.+ (n ℕ.+ (m ℕ.* n)))) ≡⟨ solve 2 (λ m n → con 2 :* (con 2 :* (con 1 :+ (m :+ (n :+ m :* n)))) :=
(con 2 :* (con 1 :+ m)) :* (con 2 :* (con 1 :+ n)))
refl m n ⟩
(2 ℕ.* (1 ℕ.+ m)) ℕ.* (2 ℕ.* (1 ℕ.+ n)) ≡⟨⟩
toℕ 2[1+ x ] ℕ.* toℕ 2[1+ y ] ∎
where
open ≡-Reasoning; m = toℕ x; n = toℕ y; xy = x * y
|x|+|y|≤cnt = ℕₚ.≤-trans (ℕₚ.+-monoʳ-≤ (size x) (ℕₚ.n≤1+n (size y))) |x|+1+|y|≤cnt
aux 2[1+ x ] 1+[2 y ] (ℕ.suc cnt) (s≤s |x|+1+|y|≤cnt) = begin
toℕ (2[1+ x ] * 1+[2 y ]) ≡⟨⟩
toℕ (2[1+ (x + y * 2[1+ x ]) ]) ≡⟨⟩
2 ℕ.* (ℕ.suc (toℕ (x + y * 2[1+ x ]))) ≡⟨ cong ((2 ℕ.*_) ∘ ℕ.suc) (toℕ-homo-+ x _) ⟩
2 ℕ.* (ℕ.suc (m ℕ.+ (toℕ (y * 2[1+ x ])))) ≡⟨ cong ((2 ℕ.*_) ∘ ℕ.suc ∘ (m ℕ.+_))
(aux y 2[1+ x ] cnt |y|+1+|x|≤cnt) ⟩
2 ℕ.* (1+m ℕ.+ (n ℕ.* (toℕ 2[1+ x ]))) ≡⟨⟩
2 ℕ.* (1+m ℕ.+ (n ℕ.* 2[1+m])) ≡⟨ solve 2 (λ m n →
con 2 :* ((con 1 :+ m) :+ (n :* (con 2 :* (con 1 :+ m)))) :=
(con 2 :* (con 1 :+ m)) :* (con 1 :+ con 2 :* n))
refl m n ⟩
2[1+m] ℕ.* (ℕ.suc (2 ℕ.* n)) ≡⟨⟩
toℕ 2[1+ x ] ℕ.* toℕ 1+[2 y ] ∎
where
open ≡-Reasoning; m = toℕ x; n = toℕ y; 1+m = ℕ.suc m; 2[1+m] = 2 ℕ.* (ℕ.suc m)
eq : size x ℕ.+ (ℕ.suc (size y)) ≡ size y ℕ.+ (ℕ.suc (size x))
eq = ℕ-+-semigroupProperties.x∙yz≈z∙yx (size x) 1 _
|y|+1+|x|≤cnt = subst (ℕ._≤ cnt) eq |x|+1+|y|≤cnt
aux 1+[2 x ] 2[1+ y ] (ℕ.suc cnt) (s≤s |x|+1+|y|≤cnt) = begin
toℕ (1+[2 x ] * 2[1+ y ]) ≡⟨⟩
toℕ 2[1+ (y + x * 2[1+ y ]) ] ≡⟨⟩
2 ℕ.* (ℕ.suc (toℕ (y + x * 2[1+ y ]))) ≡⟨ cong ((2 ℕ.*_) ∘ ℕ.suc)
(toℕ-homo-+ y (x * 2[1+ y ])) ⟩
2 ℕ.* (ℕ.suc (n ℕ.+ (toℕ (x * 2[1+ y ])))) ≡⟨ cong ((2 ℕ.*_) ∘ ℕ.suc ∘ (n ℕ.+_))
(aux x 2[1+ y ] cnt |x|+1+|y|≤cnt) ⟩
2 ℕ.* (1+n ℕ.+ (m ℕ.* toℕ 2[1+ y ])) ≡⟨⟩
2 ℕ.* (1+n ℕ.+ (m ℕ.* 2[1+n])) ≡⟨ solve 2 (λ m n →
con 2 :* ((con 1 :+ n) :+ (m :* (con 2 :* (con 1 :+ n)))) :=
(con 1 :+ (con 2 :* m)) :* (con 2 :* (con 1 :+ n)))
refl m n ⟩
(ℕ.suc 2m) ℕ.* 2[1+n] ≡⟨⟩
toℕ 1+[2 x ] ℕ.* toℕ 2[1+ y ] ∎
where
open ≡-Reasoning
m = toℕ x; n = toℕ y; 1+n = ℕ.suc n
2m = 2 ℕ.* m; 2[1+n] = 2 ℕ.* (ℕ.suc n)
aux 1+[2 x ] 1+[2 y ] (ℕ.suc cnt) (s≤s |x|+1+|y|≤cnt) = begin
toℕ (1+[2 x ] * 1+[2 y ]) ≡⟨⟩
toℕ 1+[2 (x + y * 1+2x) ] ≡⟨⟩
ℕ.suc (2 ℕ.* (toℕ (x + y * 1+2x))) ≡⟨ cong (ℕ.suc ∘ (2 ℕ.*_)) (toℕ-homo-+ x (y * 1+2x)) ⟩
ℕ.suc (2 ℕ.* (m ℕ.+ (toℕ (y * 1+2x)))) ≡⟨ cong (ℕ.suc ∘ (2 ℕ.*_) ∘ (m ℕ.+_))
(aux y 1+2x cnt |y|+1+|x|≤cnt) ⟩
ℕ.suc (2 ℕ.* (m ℕ.+ (n ℕ.* [1+2x]′))) ≡⟨ cong ℕ.suc $ ℕₚ.*-distribˡ-+ 2 m (n ℕ.* [1+2x]′) ⟩
ℕ.suc (2m ℕ.+ (2 ℕ.* (n ℕ.* [1+2x]′))) ≡⟨ cong (ℕ.suc ∘ (2m ℕ.+_)) (sym (ℕₚ.*-assoc 2 n _)) ⟩
(ℕ.suc 2m) ℕ.+ 2n ℕ.* [1+2x]′ ≡⟨⟩
[1+2x]′ ℕ.+ 2n ℕ.* [1+2x]′ ≡⟨ cong (ℕ._+ (2n ℕ.* [1+2x]′)) $
sym (ℕₚ.*-identityˡ [1+2x]′) ⟩
1 ℕ.* [1+2x]′ ℕ.+ 2n ℕ.* [1+2x]′ ≡⟨ sym (ℕₚ.*-distribʳ-+ [1+2x]′ 1 2n) ⟩
(ℕ.suc 2n) ℕ.* [1+2x]′ ≡⟨ ℕₚ.*-comm (ℕ.suc 2n) [1+2x]′ ⟩
toℕ 1+[2 x ] ℕ.* toℕ 1+[2 y ] ∎
where
open ≡-Reasoning
m = toℕ x; n = toℕ y; 2m = 2 ℕ.* m; 2n = 2 ℕ.* n
1+2x = 1+[2 x ]; [1+2x]′ = toℕ 1+2x
eq : size x ℕ.+ (ℕ.suc (size y)) ≡ size y ℕ.+ (ℕ.suc (size x))
eq = ℕ-+-semigroupProperties.x∙yz≈z∙yx (size x) 1 _
|y|+1+|x|≤cnt = subst (ℕ._≤ cnt) eq |x|+1+|y|≤cnt
toℕ-isMagmaHomomorphism-* : IsMagmaHomomorphism *-rawMagma ℕₚ.*-rawMagma toℕ
toℕ-isMagmaHomomorphism-* = record
{ isRelHomomorphism = toℕ-isRelHomomorphism
; homo = toℕ-homo-*
}
toℕ-isMonoidHomomorphism-* : IsMonoidHomomorphism *-1-rawMonoid ℕₚ.*-1-rawMonoid toℕ
toℕ-isMonoidHomomorphism-* = record
{ isMagmaHomomorphism = toℕ-isMagmaHomomorphism-*
; ε-homo = refl
}
toℕ-isMonoidMonomorphism-* : IsMonoidMonomorphism *-1-rawMonoid ℕₚ.*-1-rawMonoid toℕ
toℕ-isMonoidMonomorphism-* = record
{ isMonoidHomomorphism = toℕ-isMonoidHomomorphism-*
; injective = toℕ-injective
}
fromℕ-homo-* : ∀ m n → fromℕ (m ℕ.* n) ≡ fromℕ m * fromℕ n
fromℕ-homo-* m n = begin
fromℕ (m ℕ.* n) ≡⟨ cong fromℕ (cong₂ ℕ._*_ m≡aN n≡bN) ⟩
fromℕ (toℕ a ℕ.* toℕ b) ≡⟨ cong fromℕ (sym (toℕ-homo-* a b)) ⟩
fromℕ (toℕ (a * b)) ≡⟨ fromℕ-toℕ (a * b) ⟩
a * b ∎
where
open ≡-Reasoning
a = fromℕ m; b = fromℕ n
m≡aN = sym (toℕ-fromℕ m); n≡bN = sym (toℕ-fromℕ n)
private
module *-Monomorphism = MonoidMonomorphism toℕ-isMonoidMonomorphism-*
*-assoc : Associative _*_
*-assoc = *-Monomorphism.assoc ℕₚ.*-isMagma ℕₚ.*-assoc
*-comm : Commutative _*_
*-comm = *-Monomorphism.comm ℕₚ.*-isMagma ℕₚ.*-comm
*-identityˡ : LeftIdentity 1ᵇ _*_
*-identityˡ = *-Monomorphism.identityˡ ℕₚ.*-isMagma ℕₚ.*-identityˡ
*-identityʳ : RightIdentity 1ᵇ _*_
*-identityʳ x = trans (*-comm x 1ᵇ) (*-identityˡ x)
*-identity : Identity 1ᵇ _*_
*-identity = (*-identityˡ , *-identityʳ)
*-zeroˡ : LeftZero zero _*_
*-zeroˡ _ = refl
*-zeroʳ : RightZero zero _*_
*-zeroʳ zero = refl
*-zeroʳ 2[1+ _ ] = refl
*-zeroʳ 1+[2 _ ] = refl
*-zero : Zero zero _*_
*-zero = *-zeroˡ , *-zeroʳ
*-distribˡ-+ : _*_ DistributesOverˡ _+_
*-distribˡ-+ a b c = begin
a * (b + c) ≡⟨ sym (fromℕ-toℕ (a * (b + c))) ⟩
fromℕ (toℕ (a * (b + c))) ≡⟨ cong fromℕ (toℕ-homo-* a (b + c)) ⟩
fromℕ (k ℕ.* (toℕ (b + c))) ≡⟨ cong (fromℕ ∘ (k ℕ.*_)) (toℕ-homo-+ b c) ⟩
fromℕ (k ℕ.* (m ℕ.+ n)) ≡⟨ cong fromℕ (ℕₚ.*-distribˡ-+ k m n) ⟩
fromℕ (k ℕ.* m ℕ.+ k ℕ.* n) ≡⟨ cong fromℕ $ sym $
cong₂ ℕ._+_ (toℕ-homo-* a b) (toℕ-homo-* a c) ⟩
fromℕ (toℕ (a * b) ℕ.+ toℕ (a * c)) ≡⟨ cong fromℕ (sym (toℕ-homo-+ (a * b) (a * c))) ⟩
fromℕ (toℕ (a * b + a * c)) ≡⟨ fromℕ-toℕ (a * b + a * c) ⟩
a * b + a * c ∎
where open ≡-Reasoning; k = toℕ a; m = toℕ b; n = toℕ c
*-distribʳ-+ : _*_ DistributesOverʳ _+_
*-distribʳ-+ = comm+distrˡ⇒distrʳ *-comm *-distribˡ-+
*-distrib-+ : _*_ DistributesOver _+_
*-distrib-+ = *-distribˡ-+ , *-distribʳ-+
*-isMagma : IsMagma _*_
*-isMagma = isMagma _*_
*-isSemigroup : IsSemigroup _*_
*-isSemigroup = *-Monomorphism.isSemigroup ℕₚ.*-isSemigroup
*-1-isMonoid : IsMonoid _*_ 1ᵇ
*-1-isMonoid = *-Monomorphism.isMonoid ℕₚ.*-1-isMonoid
*-1-isCommutativeMonoid : IsCommutativeMonoid _*_ 1ᵇ
*-1-isCommutativeMonoid = *-Monomorphism.isCommutativeMonoid ℕₚ.*-1-isCommutativeMonoid
+-*-isSemiringWithoutAnnihilatingZero : IsSemiringWithoutAnnihilatingZero _+_ _*_ zero 1ᵇ
+-*-isSemiringWithoutAnnihilatingZero = record
{ +-isCommutativeMonoid = +-0-isCommutativeMonoid
; *-isMonoid = *-1-isMonoid
; distrib = *-distrib-+
}
+-*-isSemiring : IsSemiring _+_ _*_ zero 1ᵇ
+-*-isSemiring = record
{ isSemiringWithoutAnnihilatingZero = +-*-isSemiringWithoutAnnihilatingZero
; zero = *-zero
}
+-*-isCommutativeSemiring : IsCommutativeSemiring _+_ _*_ zero 1ᵇ
+-*-isCommutativeSemiring = record
{ isSemiring = +-*-isSemiring
; *-comm = *-comm
}
*-magma : Magma 0ℓ 0ℓ
*-magma = record
{ isMagma = *-isMagma
}
*-semigroup : Semigroup 0ℓ 0ℓ
*-semigroup = record
{ isSemigroup = *-isSemigroup
}
*-1-monoid : Monoid 0ℓ 0ℓ
*-1-monoid = record
{ isMonoid = *-1-isMonoid
}
*-1-commutativeMonoid : CommutativeMonoid 0ℓ 0ℓ
*-1-commutativeMonoid = record
{ isCommutativeMonoid = *-1-isCommutativeMonoid
}
+-*-semiring : Semiring 0ℓ 0ℓ
+-*-semiring = record
{ isSemiring = +-*-isSemiring
}
+-*-commutativeSemiring : CommutativeSemiring 0ℓ 0ℓ
+-*-commutativeSemiring = record
{ isCommutativeSemiring = +-*-isCommutativeSemiring
}
*-mono-≤ : _*_ Preserves₂ _≤_ ⟶ _≤_ ⟶ _≤_
*-mono-≤ {x} {u} {y} {v} x≤u y≤v = toℕ-cancel-≤ (begin
toℕ (x * y) ≡⟨ toℕ-homo-* x y ⟩
toℕ x ℕ.* toℕ y ≤⟨ ℕₚ.*-mono-≤ (toℕ-mono-≤ x≤u) (toℕ-mono-≤ y≤v) ⟩
toℕ u ℕ.* toℕ v ≡⟨ sym (toℕ-homo-* u v) ⟩
toℕ (u * v) ∎)
where open ℕₚ.≤-Reasoning
*-monoʳ-≤ : ∀ x → (x *_) Preserves _≤_ ⟶ _≤_
*-monoʳ-≤ x y≤y′ = *-mono-≤ (≤-refl {x}) y≤y′
*-monoˡ-≤ : ∀ x → (_* x) Preserves _≤_ ⟶ _≤_
*-monoˡ-≤ x y≤y′ = *-mono-≤ y≤y′ (≤-refl {x})
*-mono-< : _*_ Preserves₂ _<_ ⟶ _<_ ⟶ _<_
*-mono-< {x} {u} {y} {v} x<u y<v = toℕ-cancel-< (begin-strict
toℕ (x * y) ≡⟨ toℕ-homo-* x y ⟩
toℕ x ℕ.* toℕ y <⟨ ℕₚ.*-mono-< (toℕ-mono-< x<u) (toℕ-mono-< y<v) ⟩
toℕ u ℕ.* toℕ v ≡⟨ sym (toℕ-homo-* u v) ⟩
toℕ (u * v) ∎)
where open ℕₚ.≤-Reasoning
*-monoʳ-< : ∀ x → ((1ᵇ + x) *_) Preserves _<_ ⟶ _<_
*-monoʳ-< x {y} {z} y<z = begin-strict
(1ᵇ + x) * y ≡⟨ *-distribʳ-+ y 1ᵇ x ⟩
1ᵇ * y + x * y ≡⟨ cong (_+ x * y) (*-identityˡ y) ⟩
y + x * y <⟨ +-mono-<-≤ y<z (*-monoʳ-≤ x (<⇒≤ y<z)) ⟩
z + x * z ≡⟨ cong (_+ x * z) (sym (*-identityˡ z)) ⟩
1ᵇ * z + x * z ≡⟨ sym (*-distribʳ-+ z 1ᵇ x) ⟩
(1ᵇ + x) * z ∎
where open ≤-Reasoning
*-monoˡ-< : ∀ x → (_* (1ᵇ + x)) Preserves _<_ ⟶ _<_
*-monoˡ-< x {y} {z} y<z = begin-strict
y * (1ᵇ + x) ≡⟨ *-comm y (1ᵇ + x) ⟩
(1ᵇ + x) * y <⟨ *-monoʳ-< x y<z ⟩
(1ᵇ + x) * z ≡⟨ *-comm (1ᵇ + x) z ⟩
z * (1ᵇ + x) ∎
where open ≤-Reasoning
x*y≡0⇒x≡0∨y≡0 : ∀ x {y} → x * y ≡ zero → x ≡ zero ⊎ y ≡ zero
x*y≡0⇒x≡0∨y≡0 zero {_} _ = inj₁ refl
x*y≡0⇒x≡0∨y≡0 _ {zero} _ = inj₂ refl
x≢0∧y≢0⇒x*y≢0 : ∀ {x y} → x ≢ zero → y ≢ zero → x * y ≢ zero
x≢0∧y≢0⇒x*y≢0 {x} {_} x≢0 y≢0 xy≡0 with x*y≡0⇒x≡0∨y≡0 x xy≡0
... | inj₁ x≡0 = x≢0 x≡0
... | inj₂ y≡0 = y≢0 y≡0
2*x≡x+x : ∀ x → 2ᵇ * x ≡ x + x
2*x≡x+x x = begin
2ᵇ * x ≡⟨⟩
(1ᵇ + 1ᵇ) * x ≡⟨ *-distribʳ-+ x 1ᵇ 1ᵇ ⟩
1ᵇ * x + 1ᵇ * x ≡⟨ cong₂ _+_ (*-identityˡ x) (*-identityˡ x) ⟩
x + x ∎
where open ≡-Reasoning
1+-* : ∀ x y → (1ᵇ + x) * y ≡ y + x * y
1+-* x y = begin
(1ᵇ + x) * y ≡⟨ *-distribʳ-+ y 1ᵇ x ⟩
1ᵇ * y + x * y ≡⟨ cong (_+ x * y) (*-identityˡ y) ⟩
y + x * y ∎
where open ≡-Reasoning
*-1+ : ∀ x y → y * (1ᵇ + x) ≡ y + y * x
*-1+ x y = begin
y * (1ᵇ + x) ≡⟨ *-distribˡ-+ y 1ᵇ x ⟩
y * 1ᵇ + y * x ≡⟨ cong (_+ y * x) (*-identityʳ y) ⟩
y + y * x ∎
where open ≡-Reasoning
double[x]≡0⇒x≡0 : ∀ {x} → double x ≡ zero → x ≡ zero
double[x]≡0⇒x≡0 {zero} _ = refl
x≡0⇒double[x]≡0 : ∀ {x} → x ≡ 0ᵇ → double x ≡ 0ᵇ
x≡0⇒double[x]≡0 = cong double
x≢0⇒double[x]≢0 : ∀ {x} → x ≢ zero → double x ≢ zero
x≢0⇒double[x]≢0 x≢0 = x≢0 ∘ double[x]≡0⇒x≡0
double≢1 : ∀ {x} → double x ≢ 1ᵇ
double≢1 {zero} ()
double≗2* : double ≗ 2ᵇ *_
double≗2* x = toℕ-injective $ begin
toℕ (double x) ≡⟨ toℕ-double x ⟩
2 ℕ.* (toℕ x) ≡⟨ sym (toℕ-homo-* 2ᵇ x) ⟩
toℕ (2ᵇ * x) ∎
where open ≡-Reasoning
double-*-assoc : ∀ x y → (double x) * y ≡ double (x * y)
double-*-assoc x y = begin
(double x) * y ≡⟨ cong (_* y) (double≗2* x) ⟩
(2ᵇ * x) * y ≡⟨ *-assoc 2ᵇ x y ⟩
2ᵇ * (x * y) ≡⟨ sym (double≗2* (x * y)) ⟩
double (x * y) ∎
where open ≡-Reasoning
double[x]≡x+x : ∀ x → double x ≡ x + x
double[x]≡x+x x = trans (double≗2* x) (2*x≡x+x x)
double-distrib-+ : ∀ x y → double (x + y) ≡ double x + double y
double-distrib-+ x y = begin
double (x + y) ≡⟨ double≗2* (x + y) ⟩
2ᵇ * (x + y) ≡⟨ *-distribˡ-+ 2ᵇ x y ⟩
(2ᵇ * x) + (2ᵇ * y) ≡⟨ sym (cong₂ _+_ (double≗2* x) (double≗2* y)) ⟩
double x + double y ∎
where open ≡-Reasoning
double-mono-≤ : double Preserves _≤_ ⟶ _≤_
double-mono-≤ {x} {y} x≤y = begin
double x ≡⟨ double≗2* x ⟩
2ᵇ * x ≤⟨ *-monoʳ-≤ 2ᵇ x≤y ⟩
2ᵇ * y ≡⟨ sym (double≗2* y) ⟩
double y ∎
where open ≤-Reasoning
double-mono-< : double Preserves _<_ ⟶ _<_
double-mono-< {x} {y} x<y = begin-strict
double x ≡⟨ double≗2* x ⟩
2ᵇ * x <⟨ *-monoʳ-< 1ᵇ x<y ⟩
2ᵇ * y ≡⟨ sym (double≗2* y) ⟩
double y ∎
where open ≤-Reasoning
double-cancel-≤ : ∀ {x y} → double x ≤ double y → x ≤ y
double-cancel-≤ {x} {y} 2x≤2y with <-cmp x y
... | tri< x<y _ _ = <⇒≤ x<y
... | tri≈ _ x≡y _ = ≤-reflexive x≡y
... | tri> _ _ x>y = contradiction 2x≤2y (<⇒≱ (double-mono-< x>y))
double-cancel-< : ∀ {x y} → double x < double y → x < y
double-cancel-< {x} {y} 2x<2y with <-cmp x y
... | tri< x<y _ _ = x<y
... | tri≈ _ refl _ = contradiction 2x<2y (<-irrefl refl)
... | tri> _ _ x>y = contradiction (double-mono-< x>y) (<⇒≯ 2x<2y)
x<double[x] : ∀ x → x ≢ zero → x < double x
x<double[x] x x≢0 = begin-strict
x <⟨ x<x+y x (x≢0⇒x>0 x≢0) ⟩
x + x ≡⟨ sym (double[x]≡x+x x) ⟩
double x ∎
where open ≤-Reasoning
x≤double[x] : ∀ x → x ≤ double x
x≤double[x] x = begin
x ≤⟨ x≤x+y x x ⟩
x + x ≡⟨ sym (double[x]≡x+x x) ⟩
double x ∎
where open ≤-Reasoning
double-suc : ∀ x → double (suc x) ≡ 2ᵇ + double x
double-suc x = begin
double (suc x) ≡⟨ cong double (suc≗1+ x) ⟩
double (1ᵇ + x) ≡⟨ double-distrib-+ 1ᵇ x ⟩
2ᵇ + double x ∎
where open ≡-Reasoning
2[1+_]-double-suc : 2[1+_] ≗ double ∘ suc
2[1+_]-double-suc zero = refl
2[1+_]-double-suc 2[1+ x ] = cong 2[1+_] (2[1+_]-double-suc x)
2[1+_]-double-suc 1+[2 x ] = refl
1+[2_]-suc-double : 1+[2_] ≗ suc ∘ double
1+[2_]-suc-double zero = refl
1+[2_]-suc-double 2[1+ x ] = refl
1+[2_]-suc-double 1+[2 x ] = begin
1+[2 1+[2 x ] ] ≡⟨ cong 1+[2_] (1+[2_]-suc-double x) ⟩
1+[2 (suc 2x) ] ≡⟨⟩
suc 2[1+ 2x ] ≡⟨ cong suc (2[1+_]-double-suc 2x) ⟩
suc (double (suc 2x)) ≡⟨ cong (suc ∘ double) (sym (1+[2_]-suc-double x)) ⟩
suc (double 1+[2 x ]) ∎
where open ≡-Reasoning; 2x = double x
suc≢0 : ∀ {x} → suc x ≢ zero
suc≢0 {zero} ()
suc≢0 {2[1+ _ ]} ()
suc≢0 {1+[2 _ ]} ()
x+suc[y]≡suc[x]+y : ∀ x y → x + suc y ≡ suc x + y
x+suc[y]≡suc[x]+y x y = begin
x + suc y ≡⟨ +-comm x _ ⟩
suc y + x ≡⟨ suc-+ y x ⟩
suc (y + x) ≡⟨ cong suc (+-comm y x) ⟩
suc (x + y) ≡⟨ sym (suc-+ x y) ⟩
suc x + y ∎
where open ≡-Reasoning
0<suc : ∀ x → zero < suc x
0<suc x = x≢0⇒x>0 (suc≢0 {x})
x<suc[x] : ∀ x → x < suc x
x<suc[x] x = begin-strict
x <⟨ x<1+x x ⟩
1ᵇ + x ≡⟨ sym (suc≗1+ x) ⟩
suc x ∎
where open ≤-Reasoning
x≤suc[x] : ∀ x → x ≤ suc x
x≤suc[x] x = <⇒≤ (x<suc[x] x)
x≢suc[x] : ∀ x → x ≢ suc x
x≢suc[x] x = <⇒≢ (x<suc[x] x)
suc-mono-≤ : suc Preserves _≤_ ⟶ _≤_
suc-mono-≤ {x} {y} x≤y = begin
suc x ≡⟨ suc≗1+ x ⟩
1ᵇ + x ≤⟨ +-monoʳ-≤ 1ᵇ x≤y ⟩
1ᵇ + y ≡⟨ sym (suc≗1+ y) ⟩
suc y ∎
where open ≤-Reasoning
suc[x]≤y⇒x<y : ∀ {x y} → suc x ≤ y → x < y
suc[x]≤y⇒x<y {x} (inj₁ sx<y) = <-trans (x<suc[x] x) sx<y
suc[x]≤y⇒x<y {x} (inj₂ refl) = x<suc[x] x
x<y⇒suc[x]≤y : ∀ {x y} → x < y → suc x ≤ y
x<y⇒suc[x]≤y {x} {y} x<y = begin
suc x ≡⟨ sym (fromℕ-toℕ (suc x)) ⟩
fromℕ (toℕ (suc x)) ≡⟨ cong fromℕ (toℕ-suc x) ⟩
fromℕ (ℕ.suc (toℕ x)) ≤⟨ fromℕ-mono-≤ (toℕ-mono-< x<y) ⟩
fromℕ (toℕ y) ≡⟨ fromℕ-toℕ y ⟩
y ∎
where open ≤-Reasoning
suc-* : ∀ x y → suc x * y ≡ y + x * y
suc-* x y = begin
suc x * y ≡⟨ cong (_* y) (suc≗1+ x) ⟩
(1ᵇ + x) * y ≡⟨ 1+-* x y ⟩
y + x * y ∎
where open ≡-Reasoning
*-suc : ∀ x y → x * suc y ≡ x + x * y
*-suc x y = begin
x * suc y ≡⟨ cong (x *_) (suc≗1+ y) ⟩
x * (1ᵇ + y) ≡⟨ *-1+ y x ⟩
x + x * y ∎
where open ≡-Reasoning
x≤suc[y]*x : ∀ x y → x ≤ (suc y) * x
x≤suc[y]*x x y = begin
x ≤⟨ x≤x+y x (y * x) ⟩
x + y * x ≡⟨ sym (suc-* y x) ⟩
(suc y) * x ∎
where open ≤-Reasoning
suc[x]≤double[x] : ∀ x → x ≢ zero → suc x ≤ double x
suc[x]≤double[x] x = x<y⇒suc[x]≤y {x} {double x} ∘ x<double[x] x
suc[x]<2[1+x] : ∀ x → suc x < 2[1+ x ]
suc[x]<2[1+x] x = begin-strict
suc x <⟨ x<double[x] (suc x) suc≢0 ⟩
double (suc x) ≡⟨ sym (2[1+_]-double-suc x) ⟩
2[1+ x ] ∎
where open ≤-Reasoning
double[x]<1+[2x] : ∀ x → double x < 1+[2 x ]
double[x]<1+[2x] x = begin-strict
double x <⟨ x<suc[x] (double x) ⟩
suc (double x) ≡⟨ sym (1+[2_]-suc-double x) ⟩
1+[2 x ] ∎
where open ≤-Reasoning
pred-suc : pred ∘ suc ≗ id
pred-suc zero = refl
pred-suc 2[1+ x ] = sym (2[1+_]-double-suc x)
pred-suc 1+[2 x ] = refl
suc-pred : ∀ {x} → x ≢ zero → suc (pred x) ≡ x
suc-pred {zero} 0≢0 = contradiction refl 0≢0
suc-pred {2[1+ _ ]} _ = refl
suc-pred {1+[2 x ]} _ = sym (1+[2_]-suc-double x)
pred-mono-≤ : pred Preserves _≤_ ⟶ _≤_
pred-mono-≤ {x} {y} x≤y = begin
pred x ≡⟨ cong pred (sym (fromℕ-toℕ x)) ⟩
pred (fromℕ m) ≡⟨ sym (fromℕ-pred m) ⟩
fromℕ (ℕ.pred m) ≤⟨ fromℕ-mono-≤ (ℕₚ.pred-mono (toℕ-mono-≤ x≤y)) ⟩
fromℕ (ℕ.pred n) ≡⟨ fromℕ-pred n ⟩
pred (fromℕ n) ≡⟨ cong pred (fromℕ-toℕ y) ⟩
pred y ∎
where
open ≤-Reasoning; m = toℕ x; n = toℕ y
pred[x]<x : ∀ {x} → x ≢ zero → pred x < x
pred[x]<x {x} x≢0 = begin-strict
pred x <⟨ x<suc[x] (pred x) ⟩
suc (pred x) ≡⟨ suc-pred x≢0 ⟩
x ∎
where open ≤-Reasoning
pred[x]+y≡x+pred[y] : ∀ {x y} → x ≢ 0ᵇ → y ≢ 0ᵇ → (pred x) + y ≡ x + pred y
pred[x]+y≡x+pred[y] {x} {y} x≢0 y≢0 = begin
px + y ≡⟨ cong (px +_) (sym (suc-pred y≢0)) ⟩
px + suc py ≡⟨ cong (px +_) (suc≗1+ py) ⟩
px + (1ᵇ + py) ≡⟨ Bin+CSemigroup.x∙yz≈yx∙z px 1ᵇ py ⟩
(1ᵇ + px) + py ≡⟨ cong (_+ py) (sym (suc≗1+ px)) ⟩
(suc px) + py ≡⟨ cong (_+ py) (suc-pred x≢0) ⟩
x + py ∎
where open ≡-Reasoning; px = pred x; py = pred y
|x|≡0⇒x≡0 : ∀ {x} → size x ≡ 0 → x ≡ 0ᵇ
|x|≡0⇒x≡0 {zero} refl = refl
*-+-isSemiringWithoutAnnihilatingZero = +-*-isSemiringWithoutAnnihilatingZero
{-# WARNING_ON_USAGE *-+-isSemiringWithoutAnnihilatingZero
"Warning: *-+-isSemiringWithoutAnnihilatingZero was deprecated in v1.4.
Please use +-*-isSemiringWithoutAnnihilatingZero instead."
#-}
*-+-isSemiring = +-*-isSemiring
{-# WARNING_ON_USAGE *-+-isSemiring
"Warning: *-+-isSemiring was deprecated in v1.4.
Please use +-*-isSemiring instead."
#-}
*-+-isCommutativeSemiring = +-*-isCommutativeSemiring
{-# WARNING_ON_USAGE *-+-isCommutativeSemiring
"Warning: *-+-isCommutativeSemiring was deprecated in v1.4.
Please use +-*-isCommutativeSemiring instead."
#-}
*-+-semiring = +-*-semiring
{-# WARNING_ON_USAGE *-+-semiring
"Warning: *-+-semiring was deprecated in v1.4.
Please use +-*-semiring instead."
#-}
*-+-commutativeSemiring = +-*-commutativeSemiring
{-# WARNING_ON_USAGE *-+-commutativeSemiring
"Warning: *-+-commutativeSemiring was deprecated in v1.4.
Please use +-*-commutativeSemiring instead."
#-}